Individual vs. Collective Bargaining in the Large Firm Search Model - Christian Bauer; Jörg Lingens (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
We analyze the welfare and employment effects of different wage bargaining regimes. Within the large firm search model, we show that collective bargaining affects employment via two channels. Collective bargaining exerts opposing effects on job creation and wage setting. Firms have a stronger incentive for strategic employment, while workers benefit from the threat of a strike. We find that the employment increase due to the strategic motive is dominated by the employment decrease due to the increase in workers' threat point. In aggregate equilibrium, employment is ineciently low under collective bargaining. But it is not always true that equilibrium wages exceed those under individual bargaining. If unemployment benefits are sufficiently low, collectively bargained wages are smaller. The theory sheds new light on policies concerned with strategic employment and the relation between replacement rates and the extent of collective wage bargaining.
urn:nbn:de:bvb:19-epub-11315-9
Keywords: J30; J50; J41; 330; search; overemployment; collective wage bargaining; wage determination; Verhandlungstheorie des Lohnes; Tarifverhandlungen; Lohnbildung; Suchtheorie; Großunternehmen; Beschäftigungseffekt; Lohnniveau; Theorie